2018
DOI: 10.1080/10790268.2018.1479053
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of spasticity in spinal cord injury with botulinum toxin

Abstract: BT can be both an effective treatment for focal spasticity in SCI and a good coadjuvant for oral treatments in generalized spasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
2
18
0
1
Order By: Relevance
“…It has been considered in the last 20 years that BoNT should be indicated for people with motor incomplete SCI (ASIA Impairment Scale grades C or D according to the International Standard Neurological Classification of SCI) because this is the condition where focal spasticity is most likely to develop, despite the fact that there was a lack of publications on the use of BoNT for SCI [ 57 ]. The largest study collected data from 90 treated patients, and it showed that BoNT/A was more effective in focal spasticity in patients with AIS D, especially if they were injected for the first time in the first 6 months of evolution, and the improvement was established in terms of a decrease in tone, pain, and joint limitations and functional improvement [ 58 ]. Systematic reviews had previously been carried out on reported cases of SCI spasticity, which were either isolated cases or mixed spastic cases due to other causes [ 34 , 59 ].…”
Section: Treatment Of Spasticity In Spinal Cord Injury With Botulinum Toxinmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been considered in the last 20 years that BoNT should be indicated for people with motor incomplete SCI (ASIA Impairment Scale grades C or D according to the International Standard Neurological Classification of SCI) because this is the condition where focal spasticity is most likely to develop, despite the fact that there was a lack of publications on the use of BoNT for SCI [ 57 ]. The largest study collected data from 90 treated patients, and it showed that BoNT/A was more effective in focal spasticity in patients with AIS D, especially if they were injected for the first time in the first 6 months of evolution, and the improvement was established in terms of a decrease in tone, pain, and joint limitations and functional improvement [ 58 ]. Systematic reviews had previously been carried out on reported cases of SCI spasticity, which were either isolated cases or mixed spastic cases due to other causes [ 34 , 59 ].…”
Section: Treatment Of Spasticity In Spinal Cord Injury With Botulinum Toxinmentioning
confidence: 99%
“…In addition, it must be considered that in children below 12 years old, there are dose limits that we cannot exceed and that the first injection we make must use 50% of the estimated dose to avoid side effects due to the patient’s special predisposition. There are maximum total doses allowed for each toxin; however, due to the characteristics of the spasticity of SCI, these limits are usually exceeded [ 46 , 58 ]. The maximum doses and the recommended doses for the most frequent cases are shown in Table 3 ; they are based on previous studies and protocols, but not even the clinical trial can provide evidence for those indications and dosages [ 46 , 56 , 58 ].…”
Section: Treatment Of Spasticity In Spinal Cord Injury With Botulinum Toxinmentioning
confidence: 99%
“…Another established therapeutic use of botulinum toxin in SCI regards the pharmacological therapy of spasticity, a complication often associated with spinal trauma characterized by an abnormal muscle contraction of the limbs [108][109][110][111]. Injection of BoNT/A on specific muscles has been reported to improve mobility by counteracting spasticity in patients with spinal cord lesions [112][113][114][115][116].…”
Section: Botulinum Toxin and Spinal Cord Injuriesmentioning
confidence: 99%
“…In post-traumatic SCI, a prevalence between 60% and 80% has been reported and 35% had severe spasticity [65,66]. Although spasticity is a common disorder following SCI, few investigations have been performed to analyse the effect of BTX-A [67,68] and no studies have investigated high dose BTX-A in reducing spasticity in subjects with SCI.…”
Section: Spinal Cord Injurymentioning
confidence: 99%